PENGEMBANGAN LAPANGAN GASIFIKASI BATUBARA DAN KARAKTERISTIK MIKROSKOPIS SEAM-A UPPER DAERAH BITAHAN, RANTAU, KAB.TAPIN, KALIMANTAN SELATAN - Basuki Rahmad; Sugeng Raharjo; Eko Widi Pramudiohadi; Ediyanto _; Afif Dhiya‘uddin Pratama (PROSIDING SNAST, 2018)
The research is located in Bitahan, Rantau, South Kalimantan Province. Geological setting of Idamanggala area located in Barito Basin included in Warukin Formation Early-Middle Miocene. Rantau’s coal has a low maturity (immature) with Random vitrinite reflectance from 0.42 to 0.56 Coal rank classification : sub-bituminous coal. The average composition of Rantau’s coal maceral for vitrinite maceral group is 85.57% (vol.). Vitrinite content is relatively high in coal of Rantau that included in kerogen type III as an identifier of humic organic matter and derived from the woody tissue of higher plants (angiosperm). The vitrinite is maceral forming high methane (gas prone). Average quality (proximate test) coal of Formation Warukin: Calories 5263-5822 kcal / kg (adb), sulfur 0,10-0,20% (adb); ash 2,77-7,29% (adb); inherent moisture 12,33-24,10 % (adb); volatile matter 37,76-45,46% (adb); fixed carbon 31,90-41,28 % (adb), Total Moisture 31,25-38,13 % (Ar); relative density 1,32-1,88. Coal gasification is the process of converting coal into synthesis gas. One of the gas produced is a flammable methane gas. The process of coal gasification can be done by drilling at 2 (two) drill holes toward the coal seam which is the target of gasification ie Seam-A Upper coal seam at depth more than 100 meter. The first drill to inject oxygen (O2) is pressurized like air or water, so it will burn in the Seam-A Upper coal layer, while the second drill serves as a production well to drain raw gas to the gasification reactor for binds CO2 and eventually methane gas (CH4) will be channeled to a power plant.